2001
DOI: 10.1016/s0022-3956(01)00015-2
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 2A receptor gene polymorphism is not associated with completed suicide

Abstract: Several lines of evidence indicate that a serotonergic dysfunction is involved in the biological susceptibility to suicide. Recently, the A-1438G polymorphism of the serotonin 2A (5-HT2A) receptor gene has been suggested to be associated with suicide, but the results are inconsistent. We examined whether the A-1438G polymorphism of the 5-HT2A receptor gene was associated with suicide itself using 151 Japanese completed suicides. No significant difference in genotype distribution or allele frequencies of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 22 publications
3
25
3
Order By: Relevance
“…Our results confirm previous reports that genotype frequencies of 102T/C 5-HT 2A receptor gene polymorphism in mood disorders do not differ from healthy volunteers (Arranz et al, 1997;Bondy et al, 2000;Crawford et al, 2000;Mahieu et al, 1997;Minov et al, 2001;Tsai et al, 1999;Ono et al, 2001;Correa et al, 2002;Geijer et al, 2000). Nevertheless, we found an excess of the TC genotype in suicide attempters compared with nonattempters.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results confirm previous reports that genotype frequencies of 102T/C 5-HT 2A receptor gene polymorphism in mood disorders do not differ from healthy volunteers (Arranz et al, 1997;Bondy et al, 2000;Crawford et al, 2000;Mahieu et al, 1997;Minov et al, 2001;Tsai et al, 1999;Ono et al, 2001;Correa et al, 2002;Geijer et al, 2000). Nevertheless, we found an excess of the TC genotype in suicide attempters compared with nonattempters.…”
Section: Discussionsupporting
confidence: 91%
“…Greater 5-HT 2A binding has been reported in post-mortem brain tissue from individuals with major depression and suicide victims by some but not all studies (Stanley and Mann 1983;Mann et al, 1986;Hrdina and Du 2001;Kato et al, 1996;Ono et al, 2001;Hrdina et al, 1993;Arora and Meltzer 1989;Yates et al, 1990). Pandey et al (1995) found that higher prefrontal cortical 5-HT 2A binding was associated with greater gene expression in youth suicide.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…122 As completed suicides are more homogeneous in terms of higher lethality and are thought to be more influenced by serotonergic mechanisms than attempted suicides, 7 we and others examined whether one of the 5-HT2A receptor polymorphisms was associated with completed suicides, irrespective of the underlying clinical diagnosis. Neither the A-1438G nor the T102C polymorphism were associated with completed suicide in 151 Japanese, 123 131 Caucasian 124 or 68 Australian suicide victims. 125 However, one has to take into account that in none of these studies a psychological autopsy was available, and therefore no information about the proportion of depressed patients in these samples.…”
mentioning
confidence: 92%
“…13 In an association study, Du et al reported that the C allele of the T102C polymorphism, which is almost completely in disequilibrium with the A-1438G polymorphism, 14 was associated with suicidal ideation in major depressive disorders, 15 although no association was found between these polymorphisms and suicidal behavior itself. 12,16,17 Tryptophan hydroxylase (TPH) is the rate-limiting enzyme in serotonin biosynthesis and has a major function in regulating the serotonergic system. However, TPH activity as a pre-synaptic serotonergic marker has not been measured in the postmortem brain of suicide victims.…”
mentioning
confidence: 99%